Pemanfaatan RFID, Loadcell, dan Sensor Infrared Untuk Miniatur Penukaran Botol Plastik Bekas - Darussalam Darussalam; Arief Goeritno (Ikatan Ahli Informatika Indonesia (IAII), 2021)
An embedded system has been fabricated through the use of the RFID module, load cell, and infrared sensor assisted by the Arduino module. The objectives of this study are to design an embedded system and embed applications and measure the performance of the embedded system through validation tests. The research method was carried out for the realization of a miniature structure, the integrated wiring of electronic devices, and making an application based on Arduino software. Achievements during the validation test of the embedded system were carried out through three conditions. Miniature physique as a place for the subsystems of mechanical drive, controller, and the optimization of the layout of each device is an attempt to attain the hardware handshaking through integrated wiring. Acquiring applications is an attempt to attain soft handshaking. Achievement of hardware and software handshaking is carried out during the validation test, namely checking balances, cash withdrawals, and disposing of garbage. The exchange of garbage for money, after there is a high dimensional qualification with the criteria 3big